An analysis of collection development in the university libraries of Pakistan. Issue 1 (4th January 2016) - Khan, Ghalib; Bhatti, Rubina
Abstract : Purpose: – The study aims to explore the factors which influence collection development and management in academic libraries. In libraries and information centres, collection development is considered an essential element of the information life cycle. Collection development and management activities do not emanate from a vacuum. Several factors have a direct bearing on the way in which collections are developed and managed in the academic libraries. These factors are bridges and barriers for effective collection development and management. Design/methodology/approach: – An extensive review of the available literature was made to conduct the study. Findings: – The study found that several factors have a direct bearing on the way in which collections are developed and managed in the academic libraries. These factors include goals of collection development and management policies and procedures, user needs, collection development policies (CDPs), collection development budgets, collection evaluation to determine the strength and weaknesses of various subjects in the collections, selection of reading materials, formats in which materials are selected, the issues of access versus ownership, cooperative collection development, resource-sharing programs and legal issues in collection development and management. Originality/value: – This study provides an overview of various factors that influence collection development activities in the academic libraries. It provides an insight for the selectors of library resources to take these factors into account for building effective collections in the academic libraries of Pakistan and abroad.